Rumah septuagenarian kumpulan 7 drama pentas - Anwar Ridhwan (Nusa Centre, 2021)
Seven drama scripts that have never been staged and published, are brought to the readers this time. The book closes with two manuscripts of stories that reflect back on the history of the fight against oppression for the sake of peace - becoming a repeated tragedy.